Battery of tests for return-to-sport assessment after knee injury in athletes - Lesmana, Syahmirza Indra; Sugiyanto; Hidayatullah, M. Furqon; Doewes, Muchsin; Jusup, Sinu Andhi (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: Knee injury is a common sports injury, and exercise therapy can be guided by functional and biological tests to assess healing and readiness to return to sport. This study aimed to develop a test battery to identify the most predictive functional test in determining the success of an exercise therapy program for sports injury. Methods: A test construction methodology was used, incorporating 8 field test instruments and TGF-β1 as a biological marker. Statistical methods, including multiple correlation and Wherry Doolittle test selection, were applied to develop a functional test model supporting post-injury sports therapy. Results: This study found no significant correlation between TGF-β1 and the single leg stance (p=0.160), single leg calf raise (p=0.902), vertical jump (p=0.344), shuttle run (p=0.794), and hop tests (p=0.555). However, significant correlations were found with the sit and reach test (p<0.001; r=0.471) and hexagonal agility test (p=0.019; r=-0.318). Multivariate linear regression showed that the single leg stance, sit and reach, and hexagonal agility tests were predictors of TGF-β1, with the single leg stance and sit and reach tests explaining 23% of its variance. Conclusion: Test battery arrangement for functional tests that were considered predictive include single leg stance and sit and reach tests, with low correlation values, which two tests in the form of single leg balance and sit and reach tests have a relationship with tissue healing. Additionally, several other tests were designed to determine the ability of athletes to RTS.